Imaginative Interconnection and its Relationship to Spatial Thinking Among Preparatory School Students in Mathematics - Salam Kadhim Inad; Dr. Lina Fouad Jawad (Migration Letters, 2023)
The aim of the research is to identify the nature of the correlation between imaginative interconnection and spatial thinking. Correlational descriptive methodology has been adopted. The research community, which represents fourth-grade students in governmental preparatory and secondary schools affiliated to the General Directorate of Education of Karbala / Center, was identified for the academic year (2022-2023). The number of the sample was (381) male and female students (156) male and (225) female students, and for the purpose of collecting data for the research, two tests were constructed: the imaginative interconnection test and the spatial thinking test. The psychometric properties of them were confirmed, and then the appropriate statistical methods were adopted to analyze the results, and the results indicated that the students of the research sample do not possess imaginative interdependence or spatial thinking, and there is a direct positive correlation between imaginative interconnection and spatial thinking in the research sample.